Al- Ghazālī’s approach in defending the Islamic faith - Abdull Rahman Mahmood,; Abu Suailk, Ibrahim Hamed Hassan; Wan Haslan Khairuddin,; Nur ‘Izzati Hashim, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Al-Ghazālī is considered as imam (the most prominent) in epistemological critique and religious sects during his time, and one of the most prominent in defending the belief of Ahl al-Sunnah wa al-Jamā‘ah (Sunni Muslims, Sunnis, Sunnites). He is also considered one of the most prominent of theorizing of the Ash‘arī theology (Asharites or Ashʿarism) and Sufi thought. He was able to purify philosophy from superstition, and clarifies what is bad from what is sound, and he is considered as mujaddid (reformer) in his time. He was also distinguished by his intelligence, quality of writing, and erudition, as the objectives of the research were the manifestation of al-Ghazālī’s approach in defending the Islamic faith and his opinion on philosophy, theology, mysticism, and al-Bāṭiniyyah (The Sect of Batiniyya; esotericism) through studying his position in his book al-Iqtiṣād fī al-Iʿtiqād (The Moderation in Belief), Tahāfut al-Falāsifah (The Incoherence of the Philosophers), al-Munqidh min al-Ḍalāl (The Rescuer from Error) and Fadā’ih al-Bāṭiniyyah (The Infamies of the Esotericists). His positions were studied according to the historical, inductive, analytical, and critical research method. The study found that al-Ghazālī was able to be the master of his time in defending and establishing the belief of Ahl al-Sunnah wa al-Jamā‘ah, as he was also aware of the war to the al-Bāṭiniyyah and scholars, sultans, and the common people were charged with its war. Likewise, al-Ghazālī worked on establishing the Islamic faith and demonstrating it with textual and rational evidence. He criticized ‘Ilm al-Kalām (Islamic scholastic theology) and aiming it in accordance with the Islamic faith, and its use in defending and defining the Islamic faith and called for it to be preserved from the common people and to be used only in defence of the Islamic faith.